An investigation of citizenship participation of young adults with and without cerebral palsy - Yeung, Ho Yi Polly (Curtin University, 2009)
Citizenship participation by young adults has reciprocal benefits for both individuals and society. Capacity to participate in activities that positively influence the community is indicative of healthy individuals and healthy communities. While there are some studies on citizenship participation among adolescents, little empirical evidence exists regarding the meaning of, or practical participation in citizenship activities by young adults in contemporary Australia society, and particularly those who have a disability such as cerebral palsy (CP).This study investigated citizenship participation and identified factors that influenced citizenship participation in young adults with and without a disability, particularly CP. The study occurred in three phases: (1) a qualitative phase; (2) a quantitative, cross-sectional phase; and (3) a consultation phase.The aim of Phase 1 was to develop a measurement of citizenship participation based on literature and consultation with key stakeholders. Before proceeding to the item development, the ideas of how young adults in general perceived the underlying meanings of citizen participation and how they classified social and civic activities were explored through focus groups and individual interviews. A pool of 36 items was initially developed based on a critical review of participation instruments. The process of developing a suitable measurement was undertaken by item reduction, thus generating a list of 29 items. This led to the development of a self-report survey instrument of the Citizenship Inventory (CI) to measure citizenship participation. Psychometric properties of the CI were evaluated.Phase 2 involved identifying potential factors influencing citizenship participation. Supported by qualitative findings and propositions in the literature, it was predicted that citizenship participation was shaped by a number of factors labelled as civic communication, sense of place, life values and physical and social conditions, via the mediators of self-efficacy and life satisfaction. Measures of proposed independent variables and the two mediating factors identified above were then employed with a sample of 434 typical young adults, using a cross-sectional survey design. Structural Equation Modelling (SEM) was employed to investigate the interrelationships of the variables and for testing the goodness-of-fit. The identified variables contributing to citizenship participation in the typical young adults were used to compare against 60 young adults with CP.The results from modelling demonstrated that: 1) citizenship participation is influenced by the personal, social and environmental factors, which is multidimensional and subject to ongoing changes; 2) early positive activity participation creates later engagement in citizenship activities; 3) young adults’ social contexts are important socializing agents that promote citizenship participation; 4) young adults’ values influence civic participation; and 5) life satisfaction and self-efficacy are important mediating factors of citizenship participation.Similar to the typical young adults, young adults with CP developed their capacity for civic service and participation through social relationships and social memberships (formal and informal). The overall results suggest that that young adults with and without disabilities must be supported across many contexts – homes, jobs, social and community situations – to utilize their skills and abilities to actively participate in citizenship activities.Phase Three involved consulting key stakeholders, based on the research findings from the previous two phases, to identify key priorities for enhancing citizenship participation specifically for young adults with CP. These key priorities in turn helped shaping a framework of recommendations for future directions on how to promote and sustain citizenship participation in young adults with CP. The expert panel consisted of eight stakeholders who identified key priorities during a group discussion meeting using Nominal Group Techniques (NGT). Several key topics were evident in this list of priorities nominated by this group. Many of the ideas endorsed by the expert panel on enhancing citizenship participation mirrored the outcomes from the citizenship participation model. They stemmed from the principles of focusing on positive social networks, ongoing skills development, providing customised services, support and information, adopting a holistic lifespan perspective, and linking and providing real-world opportunities and experiences. Priorities identified were grouped into four main recommendations: (1) customise the types of services for each individual; (2) develop strategies to increase positive family and peer support; (3) young adults with a disability seen as competent community builders; and (4) building individual capacity.The present research sought to add to the current knowledge in understanding the changing experiences of citizenship participation of young adults living in Australia and whether young adults with a disability, particularly those with CP shared the same or different citizenship experiences as their non-disabled peers. Findings demonstrate that ideas about citizenship participation are not homogenous as they depend on circumstances. For young adults with and without CP, their citizenship identity is believed to be shaped by age, by societal expectations and by personal experiences. This thesis provides practical implications and a framework for service providers and policy makers that can be implemented to promote positive citizenship participation. This thesis also provides a rationale for further research to investigate other methodologies that enables researchers to explore the positioning and experiences of young adults’ participation in social and civic actions in this changing world.